Implementasi Regresi Logistik Biner Stratifikasi Pada Pemodelan Stunting Untuk Anak Balita Di Kabupaten Gorontalo - Ningsih, Setia; Madonsa, Muhammad Rifai; Mahmud, Sri Lestari; Djakaria, Ismail; Nasib, Salmun K (Department of Mathematics, Universitas Negeri Gorontalo, 2024)
Stunting is a condition where toddlers fail to grow due to chronic malnutrition in the first 1000 days of life (HPK). Therefore, stunting cases in Gorontalo Province, especially in Gorontalo Regency, are among the cases that need to be addressed as soon as possible. The data used is secondary data from each Puskesmas in Gorontalo Regency, to see the factors that have a significant effect on the incidence of stunting in Gorontalo Regency in urban and rural areas using the stratified binary logistic regression method. In this study, the independent variables used were Gender, Birth Weight, Birth Height, Toddler Age and Nutritional Status. The test results using the stratified binary logistic regression method show that for urban strata there are 3 significant variables, namely Birth Weight, Age of Toddlers and Nutritional Status, then for rural strata there are 2 significant variables, namely Age of Toddlers and Nutritional Status. Wald test results show that there are differences between urban and rural areas.